2020
DOI: 10.1101/2020.06.09.142141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The plant endoplasmic reticulum is both receptive and responsive to pathogen effectors

Abstract: 15The endoplasmic reticulum (ER) is the entry point to the secretory pathway and, as such, is 16 critical for adaptive responses to biotic stress, when the demand for de novo synthesis of 17 immunity-related proteins and signalling components increases significantly. Comprised of a 18 network of interconnected tubules and cisternae, the architecture of the ER is highly 19 pleomorphic and dynamic, rapidly remodelling to meet new cellular requirements. During 20 infection with the hemi-biotrophic phytopathogen, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…The A. thaliana ethylene-responsive factor 19 gene (AtERF019) mediates plant susceptibility to P. parasitica through suppression of PTI [28]. P. parasitica have developed strategies to suppress PTI through ER-localised effectors during the biotrophic relationship [21]. Transcriptomic analysis of N. tabacum's molecular response to P. parasitica found defence to oomycetes and other essential plant defence mechanisms were suppressed during the interaction [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A. thaliana ethylene-responsive factor 19 gene (AtERF019) mediates plant susceptibility to P. parasitica through suppression of PTI [28]. P. parasitica have developed strategies to suppress PTI through ER-localised effectors during the biotrophic relationship [21]. Transcriptomic analysis of N. tabacum's molecular response to P. parasitica found defence to oomycetes and other essential plant defence mechanisms were suppressed during the interaction [29].…”
Section: Discussionmentioning
confidence: 99%
“…An effector protein PpRxLR2 has been found to suppress N. benthamiana immunity by targeting a yet unknown plant susceptibility gene [20]. While Breeze et al [21] have shown ER to be an essential target of RxLR-type effectors, which induce a rapid reconfiguration of the organelle coincidently with the suppression of host defences and initial pathogen multiplication.…”
Section: Introductionmentioning
confidence: 99%
“…The interconnected tubular network of the ER can extend throughout the cytoplasm from early endosome to PM, to cell-to-cell junctions, facilitating communication and the regulation of adaptive biotic stress responses. Due to both the receptive and the responsive nature of the ER ( Breeze et al, 2020 ), it is a common subcellular target of pathogen effectors to manipulate host immunity and to hijack the secretory pathway to enable completion of the pathogen life cycle ( McLellan et al, 2013 ; Jing et al, 2016 ; Fan et al, 2018 ; Meisrimler et al, 2019 ; Tsai et al, 2019 ). In oomycetes up to 17% of the effector secretome targets ER localized host proteins, e.g., ER-localized NAC transcription factors and ER luminal binding immunoglobulin proteins (BiPs; Khan et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
“…Stromules may also facilitate the clustering of chloroplasts with the nucleus since they have been shown to move along microtubules and anchored by actin filaments [32]. In addition, pathogen-derived effectors may also achieve the same end without stromules by promoting peri-nuclear clustering of chloroplasts [17,35].…”
Section: Stromulesmentioning
confidence: 99%
“…The outer membrane of the nuclear envelope is continuous with the endoplasmic reticulum membrane (ER; Figure 1) [35] and consequently, the ca. 50 nm wide perinuclear space between the inner and outer nuclear membrane is contiguous with the ER lumen [36].…”
Section: Nature Of the Linkages-the Nuclear Envelopementioning
confidence: 99%